2018
DOI: 10.1155/2018/3481783
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Genome-Wide Analysis of Gene Expression and DNA Copy Number Variations Highlights Stem Cell-Related Pathways in Small Cell Esophageal Carcinoma

Abstract: Purpose/Objectives. Primary small cell esophageal carcinoma (SCEC) represents a rare and aggressive malignancy without any prospective clinical trial or established treatment strategy at present. Although previous studies have indicated similarities between SCEC and small cell lung cancer (SCLC) in terms of their clinical manifestations, pathology, and morphology, very little genetic information is available on this highly malignant tumor. At present, patients with SCEC are staged and treated according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…The KEGG analysis identified that the differentially expressed genes were enriched in the following pathways: cell cycle, DNA replication, p53-signaling pathway, and other pathways. These signaling pathways are important in multicellular eukaryotes, and they are not only involved in the processes of cell proliferation, differentiation, and apoptosis but also in the regulation of gynecological diseases, viral infections, and other physiological processes 30 …”
Section: Discussionmentioning
confidence: 99%
“…The KEGG analysis identified that the differentially expressed genes were enriched in the following pathways: cell cycle, DNA replication, p53-signaling pathway, and other pathways. These signaling pathways are important in multicellular eukaryotes, and they are not only involved in the processes of cell proliferation, differentiation, and apoptosis but also in the regulation of gynecological diseases, viral infections, and other physiological processes 30 …”
Section: Discussionmentioning
confidence: 99%
“…After an overall scrutiny, the datasets of GSE100942 [ 15 ] and GSE111044 [ 16 ] were selected as they suited the inclusion standards we set up. Moreover, both of them had been created recently, in the past 5 years, which met the need for timeliness.…”
Section: Methodsmentioning
confidence: 99%
“…Slides were scanned using the Agilent G2565CA scanner. Data were extracted with Feature Extraction software (v9.1 Agilent Technologies) and analyzed with Genomic Work Bench 11.0.1, Agilent Cytogenomics 5.0 and GeneSpring GX 14.5, as described elsewhere ( 5 ). The algorithm used was Aberration Detection Method 2 (ADM-2), applying the following filters: threshold=6; minimum number of probes in region=3; and Log2Ratio >0.25 and log2Ratio <-0.25 were defined as copy number gains and losses, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…To identify the significant genes that exhibited CNA and gene expression alterations, we integrated the significant CNAs and DEGs using GeneSpring software GX 14.5 (Agilent Technologies) as described elsewhere ( 5 ).…”
Section: Methodsmentioning
confidence: 99%